Effect of Strength Activity Index of Fly Ash on Concrete Performance - YIN Shaoqing; WANG Chunhui; WU Qianwen; FANG Peng (Renmin Zhujiang)
To ascertain the influence laws of the strength activity index of fly ash on concrete performance,we compound fly ash with different strength activity indexes for concrete performance tests and compare the influence of fly ash on mechanical properties,deformation properties,and durability of concrete.The experimental results reveal that within the range of the selected strength activity indexes of fly ash,the same design index of concrete all meets the design requirements,and the relevant indexes of hardened concrete and the strength activity index of fly ash maintain the same growth trend.